2020
DOI: 10.7759/cureus.8972
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Male Breast Cancer Patient with CHEK2*1100delC Mutation

Abstract: Male breast cancer (MBC) is a rare disease that accounts for less than one percent of all breast cancers. The association between BRCA1 and BRCA2 mutations and MBC has been well-established; recent data suggest that CHEK2 1100delC heterozygosity is also associated with an increased risk of MBC. Herein, we present the case of a 47-year-old male who was initially diagnosed with bilateral symmetric gynecomastia on a diagnostic mammogram performed for right breast palp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Men with BRCA1/2 mutations have an increased risk for BC: 7-8% with BRCA2 mutations and 1% with BRCA1 mutation, compared to 0.1% lifetime risk in the general population [116]. In addition, the CHEK2 mutation has also been associated with an increased risk of MBC [117]. Rates of the CHEK2 mutation seem to be higher in some countries compared to others, such as in Northern European countries, but are rare in Australia, Spain, and Ashkenazi Jewish people [117].…”
Section: Biological Sex-and Gender-related Disparity In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Men with BRCA1/2 mutations have an increased risk for BC: 7-8% with BRCA2 mutations and 1% with BRCA1 mutation, compared to 0.1% lifetime risk in the general population [116]. In addition, the CHEK2 mutation has also been associated with an increased risk of MBC [117]. Rates of the CHEK2 mutation seem to be higher in some countries compared to others, such as in Northern European countries, but are rare in Australia, Spain, and Ashkenazi Jewish people [117].…”
Section: Biological Sex-and Gender-related Disparity In Breast Cancermentioning
confidence: 99%
“…In addition, the CHEK2 mutation has also been associated with an increased risk of MBC [117]. Rates of the CHEK2 mutation seem to be higher in some countries compared to others, such as in Northern European countries, but are rare in Australia, Spain, and Ashkenazi Jewish people [117]. Szwiec et al (2021) reviewed a lot of studies that showed that male patients with mutations in the PALB2 gene have a seven-fold increased risk of MBC [118].…”
Section: Biological Sex-and Gender-related Disparity In Breast Cancermentioning
confidence: 99%